Assessment of injury current during leadless pacemaker implantation. (15th January 2021) - Breitenstein, Alexander; Saguner, Ardan M.; Gasperetti, Alessio; Hofer, Daniel; Koepfli, Pascal; Regoli, François; Steffel, Jan
Abstract: Background: Leadless pacemakers are an established treatment option for bradyarrhythmias. Similar to conventional transvenous pacemakers, satisfying pacing values during implantation are targeted for optimal long-term device function. The objective is to investigate the role of a local injury current (IC) in leadless pacemaker implantations. Method: The IC, sensing value, capture threshold and impedance were collected in 30 consecutive patients receiving a leadless pacemaker. Results: 39 EGMs were recorded from 30 patients (including 9 device repositions). An IC was detected in 15 cases (38%). At implantation, the presence of an IC was associated with a significantly lower sensing (7.1 ± 3.7 mV vs 12.0 ± 4.0 mV; P  = 0.004) and a higher capture threshold (median threshold 1.13 V at 0.24 ms [0.50–2.00] vs 0.50 V at 0.24 ms [0.25–0.75]; P  = 0.002) and with a 26 fold higher likelihood of device repositioning compared to the absence of an IC (OR 26.3 [2.79–248], P  < 0.001). Patients with an IC in their final implant position had a lower sensing (9.3 ± 4.4 mV vs 13.6 ± 4.7 mV at implantation, P  = 0.04), while the initially similar capture threshold was lower after 24 h in the IC group. After 2 weeks, all parameters were similar between the two groups. Conclusions: Our study shows that an IC can readily be observed during leadless pacemaker implantation associated with a lower sensing and a higher capture threshold at implantation but with similar to even better values during follow-up. Highlights: A local injury current can be observed during leadless pacemaker implantation It's presence is associated with impaired ventricular sensing and capture threshold at implantation, but improves over time This observation is relevant because unnecessary device repositioning could be avoided